Impact of Antibiotics on the Lung Microbiome and Lung Function in Children With Cystic Fibrosis 1 Year After Hospitalization for an Initial Pulmonary Exacerbation. (12th September 2022) - Inam, Zaina; Felton, Erin; Burrell, Aszia; Chaney, Hollis; Sami, Iman; Koumbourlis, Anastassios C; Freishtat, Robert J; Zemanick, Edith T; Crandall, Keith A; Hahn, Andrea
Abstract: Background: Cystic fibrosis (CF) is characterized by recurrent pulmonary exacerbations (PEx) and lung function decline. PEx are frequently treated with antibiotics. However, little is known about the effects of antibiotics on the airway microbiome of persons with CF over time. The purpose of this study was to evaluate changes in the microbiome and lung function in persons with CF over 1 year following an initial study pulmonary exacerbation (iPEx). Methods: Twenty children aged ≤18 years with CF were enrolled in the study, which occurred prior to the routine administration of highly effective modulator therapy. Respiratory samples and spirometry were obtained at a minimum of quarterly visits and up to 1 year after an iPEx. Metagenomic sequencing was performed, and bacterial taxa were assigned using MetaPhlAn 2.0. Paired t test, analysis of variance, and generalized least squares regression were used to compare outcome variables. Results: The mean age of study participants at the time of the iPEx was 10.6 years. There were 3 ± 1.6 PEx treated with antibiotics per person during the study period. Bacterial richness was similar at 1 year compared to iPEx (40.3 vs 39.3, P = .852), whereas the mean Shannon diversity index was significantly higher at 1 year (2.84 vs 1.62, P < .001). The number of PEx treated with antibiotics was not associated with changes in microbial diversity but was associated with changes in lung function. Conclusions: In our 1-year prospective study, we found that microbial diversity increased despite decreases in lung function associated with repeated PEx events requiring antibiotic therapy. Abstract : In our study of children with cystic fibrosis hospitalized for intravenous antibiotic treatment of an initial pulmonary exacerbation, microbial diversity remained high despite decreases in lung function associated with repeated exacerbations requiring antibiotic therapy over 1 year.